Gene‐diet‐interactions in folate‐mediated one‐carbon metabolism modify colon cancer risk. Issue 4 (7th September 2012) - Liu, Amy Y.; Scherer, Dominique; Poole, Elizabeth; Potter, John D.; Curtin, Karen; Makar, Karen; Slattery, Martha L.; Caan, Bette J.; Ulrich, Cornelia M.; Ulrich, Cornelia M.; Miller, Joshua W.
<x xml:space="preserve">Abstract</x> Scope The importance of folate‐mediated one‐carbon metabolism (FOCM) in colorectal carcinogenesis is emphasized by observations that high dietary folate intake is associated with decreased risk of colon cancer (CC) and its precursors. Additionally, polymorphisms in FOCM‐related genes have been repeatedly associated with risk, supporting a causal relationship between folate and colorectal carcinogenesis. Methods and results We investigated ten candidate polymorphisms with defined or probable functional impact in eight FOCM‐related genes (SHMT1, DHFR, DNMT1, MTHFD1, MTHFR, MTRR, TCN2, and TDG) in 1609 CC cases and 1974 controls for association with CC risk and for interaction with dietary factors. No polymorphism was statistically significantly associated with overall risk of CC. However, statistically significant interactions modifying CC risk were observed for DNMT1 I311V with dietary folate, methionine, vitamin B2, and vitamin B12 intake and for MTRR I22M with dietary folate, a predefined one‐carbon dietary pattern, and vitamin B6 intake. We observed statistically significant gene‐diet interactions with five additional polymorphisms. Conclusion Our results provide evidence that FOCM‐related dietary intakes modify the association between CC risk and FOCM allelic variants. These findings add to observations showing that folate‐related gene‐nutrient interactions play an important role in modifying the risk of CC.